A Framework for Enhancing Privacy and Anonymity in Blockchain-Enabled IoT Devices - Saad, Muhammad; Bhutta, Muhammad Raheel; Kim, Jongik; Chung, Tae Sun (Computers, Materials and Continua, 2024)
With the increase in IoT (Internet of Things) devices comes an inherent challenge of security. In the world today, privacy is the prime concern of every individual. Preserving one’s privacy and keeping anonymity throughout the system is a desired functionality that does not come without inevitable trade-offs like scalability and increased complexity and is always exceedingly difficult to manage. The challenge is keeping confidentiality and continuing to make the person innominate throughout the system. To address this, we present our proposed architecture where we manage IoT devices using blockchain technology. Our proposed architecture works on and off blockchain integrated with the closed-circuit television (CCTV) security camera fixed at the rental property. In this framework, the CCTV security camera feed is redirected towards the owner and renter based on the smart contract conditions. One entity (owner or renter) can see the CCTV security camera feed at one time. There is no third-party dependence except for the CCTV security camera deployment phase. Our contributions include the proposition of framework architecture, a novel smart contract algorithm, and the modification to the ring signatures leveraging an existing cryptographic technique. Analyses are made based on different systems’ security and key management areas. In an empirical study, our proposed algorithm performed better in key generation, proof generation, and verification times. By comparing similar existing schemes, we have shown the proposed architectures’ advantages. Until now, we have developed this system for a specific area in the real world. However, this system is scalable and applicable to other areas like healthcare monitoring systems, which is part of our future work.
Keywords: Anonymity; Block-chain; Closed circuit television; Contract conditions; One-time; Privacy; Property; Proposed architectures; Security cameras; Trade off; anonymity; blockchain; IoT; Privacy; smart contracts